Sous-section I. le discours sur la dévalorisation : féminisation des métiers de la justice, la dévalorisation en questions - Lapeyre, Nathalie (La féminisation des métiers de la justice, 2011)
Après cinquante ans d'émancipation féminine, la féminisation des professions de justice est caractérisée par divers obstacles entravant les différentes voies d'accès à ces métiers. La place des femmes dans le notariat est présentée dans un premier temps, puis les réactions à la féminisation de la justice sont observées dans les discours et dans le droit. L'étude, d'angle français, est enrichie de deux exemples sur la féminisation de la justice en Colombie et au Japon.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discriminations; droit; europe; fem7000; france; féminisation des professions; rapports sociaux de sexe; régions géographiques; science politique et droit; thématiques; travail

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique